Evaluación del desempeño de desemulsificantes con diferentes estructuras químicas en la separación de emulsiones agua -en- crudo (2017)
"The presence of water in the oil extracted from the field is a problem that affects the hydrocarbon industry at strategic points such as transportation and refining. Effectively separating the water from the oil prior to the transportation process can represent a substantial decrease in operating costs, as it would avoid extra costs in preparing the oil prior to its refinement. This experimental study aims to evaluate the ability to separate water-in-oil emulsions from several agents, in order to establish a relationship between the chemical structure of the demulsifier and its effectiveness with respect to the type of crude study. A series of bottle tests was developed in which water-in-oil emulsions were brought into contact with four de-emulsifying substances to establish, through continuous monitoring, the effectiveness of each substance." -- Tomado del Formato de Documento de Grado.